PENGGUNAAN MEDIA POWERPOINT UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR - R. TUTIK YUSRIYANTI (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
The purpose of this study was to determine the use of powerpoint media to increase motivation and learning outcomes of art and culture with materials for drawing decorative flora and fauna for class VIIG students of SMP Negeri 24 Surakarta in the second semester of the academic year 2021/2022. This research was conducted in the second semester of the academic year 2021/2022. The research subjects were 31 students of class VIIG of SMP Negeri 24 Surakarta. With the research target is the motivation and learning outcomes of art and culture materials for drawing decorative flora and fauna. Tool to collect data by observation to determine student learning motivation, learning outcomes of art and culture carried out a performance drawing test. This study uses 3 data analyzes, namely initial conditions, cycle 1 data, and cycle 2 data analyzed using comparative description techniques followed by reflection. The method used is to form large groups, small groups using powerpoint media are carried out by drawing performance tests to determine the increase in learning outcomes. This research model uses 4 stages of action: planning, action, observation, and reflection. Based on the results of the study, it was concluded that there had been an increase in the motivation indicator data for cycle 1, indicator 1) 81%, 2) 82%, 3) 87, cycle 2 increased to indicator 1) 83%, 2) 84%, 3) 90%. While the data on learning outcomes in cycle 1, the lowest score was 70, the highest score was 87, the average value was 77, there were 2 students who had not completed, cycle 2 the lowest score was 75, the highest score was 90, the average value was 79, and all the students completed. ABSTRAKTujuan Penelitian ini adalah mengetahui penggunaan media powerpoint untuk meningkatkan motivasi dan hasil belajar seni budaya materi menggambar ragam hias flora fauna bagi siswa kelas VIIG SMP Negeri 24 Surakarta pada semester dua tahun pelajaran 2021/2022.Penelitian ini dilakukan pada semester dua tahun pelajaran 2021 / 2022. Subyek penelitian 31 siswa kelas VIIG SMP Negeri 24 Surakarta. Dengan sasaran penelitian adalah motivasi dan hasil belajar seni budaya materi menggambar ragam hias flora fauna. Alat untuk pengumpulkan data dengan observasi untuk mengetahui motivasi belajar siswa, hasil belajar seni budaya dilakukan test menggambar unjuk kinerja. Penelitian ini menggunakan 3 analisis data yaitu kondisi awal, data siklus 1, dan data siklus 2 dianalisis dengan menggunakan teknik diskripsi komparatif dilanjutkan refleksi. Metode yang digunakan adalah membentuk kelompok besar, kelompok kecil dengan penggunaan media powerpoint dilakukan test menggambar unjuk kinerja untuk mengetahui peningkatan hasil belajar. Model penelitian ini menggunakan 4 tahapan tindakan : perencanaan, tindakan, observasi, refleksi.Berdasarkan hasil penelitian disimpulkan sudah mengalami peningkatan data indikator motivasi siklus 1, indikator 1) 81%, 2) 82 %, 3) 87 seklus 2 meningkat menjadi, indiKator 1) 83%, 2) 84%, 3) 90%. Sedangkan data hasil belajar siklus 1 nilai tertendah 70, nilai tertinggi 87, nilai rata – rata 77, ada 2 siswa yang belum tuntas, siklus 2 nilai terendah 75, nilai teringgi 90, nilai rata – rata 79, dan semua siswa tuntas.